(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article focuses on innovative approaches, technologies and their importance in the development of competence of future engineers, emphasizing that the integration of education, science, production with society is one of the important needs in the field of personnel training. and comments on the cluster approach as a modern priority direction in the field of science, production and education are presented.